PARASITIC MIOSITIS ASSOCIATED A INFESTATION BY TRICHINELLA IN MYRMECOPHAGA TRYDACTILA: REPORT OF CASE IN VENEZUELA - Morales Briceño, Abelardo (2009)
The aim is report a case of myositis associated with the genus Trichinella parasite in a giant anteater Myrmecophaga trydactila a bear at the zoo "El Pinar" Caracas, Venezuela. With a history of lameness of hind limbs, chronic dermatitis draining in recurrent femoral region, cervical and axillary, bacteraemia and septicaemia. Necropsy was performed systematically by the techniques described for pets. Tissue sections were taken for histopathological examination and were processed by conventional methods of histological processing. Samples were taken from stomach contents and faeces for parasitological studies using the technique of flotation. Gross examination revealed marked chronic wasting. Severe chronic exudative dermatitis with secondary bacterial infection. Evidenced hidroperitoneo marking. Focal nodular chronic erosive gastritis. Enteritis segmental duodenal mucosa and chronic colitis. Hepatomegaly with foci of fibrosis in the parenchyma. Petequial cortical hemorrhage in adrenal glands bilaterally. Nodular myositis in semi membranous muscle and tendon of semi hind limbs. The histological sections showed: chronic dermatitis characterized by abundant neutrophil infiltration polimorfonuclear mixed degenerate and few eosinophils, lymphocytes and mononuclear infiltrate plasmocitic. Lymphocytic focal myositis is observed in the presence of cysts intermiofibrilar larval forms of approximately 800 to 900μ, carried away on their own, lace sides, surrounded by a dense capsule of fibrous tissue, focal calcification and fibroplasic response. The study was consistent with eggs coprological Trichinella sp.